Older people's views about ageing well in a rural community. Issue 11 (22nd November 2021) - Neville, Stephen; Napier, Sara; Adams, Jeffery; Shannon, Kay; Clair, Valerie Wright-St
Abstract: Maintaining physical, psychological and social wellbeing is integral to older adults being able to age well in their community. Therefore, an environment that facilitates and supports ageing well is imperative. The aim of this study was to explore the views of older people about their preparation for ageing well in a rural community. Forty-nine community-dwelling older people aged between 65 and 93 years participated in a semi-structured and digitally recorded interview. The resulting qualitative data were analysed using a thematic approach. Three main themes were identified: (a) 'sensible planning: the right place and the right people'; (b) 'remaining independent: "it's up to me"'; and (c) 'facing challenges: "accepting my lot"'. Findings from this study identify that across all age groups, these older people were actively and realistically preparing for ageing well. All valued their independence, believing individually they were responsible for being independent and planning for their future. Consequently, environmental planners, policy makers and practitioners need to understand that older people are a heterogeneous group and ageing policies should be geared towards older people's individual abilities and circumstances. Consideration of diversity enables inclusion of older people with a wide range of abilities and needs to achieve the perceived goals of ageing well.